PERBANDINGAN PENERBITAN OBLIGASI PADA PASAR MODAL KONVENSIONAL DENGAN OBLIGASI SYARIAH (SUKUK) PADA PASAR MODAL SYARIAH DI INDONESIA - Rayhanil Jannah; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Needs funds in the company in considerable amounts and require a long time to restore it, the company can make the issuance of bonds which are long-term debt securities issued by companies that offer both conventional capital markets with the aim sharia in order to be purchased by investors who memilii excess funds meant for investment. Implementation of conventional bonds an Islamic bonds have in common. There are differences between conventional bonds and Islamic bonds contained in the sources of law, publishing mechanisms and processes issuers of debt payments to investors, where conventional bonds basic of on positive law and implement the system of interest, while the Islamic bond basic to fatwa.The purpose of this paper is: first, the comparison of bond issue on the capital markets conventional and Islamic bonds in the Islamic capital market and secondly, the protection of the rights of investors investing through bonds conventional and Islamic bonds.This type of research can be classified dallam kind of normative juridical research, because this research is to do with the data written to examine the literature data plus supplementary data from, primary data, secondary data and tertiary data collection techniques in this study witht hemethod literature.The results of the study there are three main issues that can be inferred. First, a comparison bond issuance in the conventional capital market with Islamic bonds in the Islamic capital market. Second, the protection of investors investing through conventional bonds and Islamic bonds. Third, the lack of certainty source of law in issuing securities in the Islamic capital market.Key words: Comparison-Publishing-Bond-Investor.